Targeting Inflammation in Emerging Therapies for Genetic Retinal Disease - Ishaq A. Viringipurampeer; Abu E. Bashar; Cheryl Y. Gregory-Evans; Orson L. Moritz; Kevin Gregory-Evans (International Journal of Inflammation)
Genetic retinal diseases such as age-related macular degeneration and monogenic diseases such as retinitis pigmentosa account for some of the commonest causes of blindness in the developed world. Diverse genetic abnormalities and environmental causes have been implicated in triggering multiple pathological mechanisms such as oxidative stress, lipofuscin deposits, neovascularisation, and programmed cell death. In recent years, inflammation has also been highlighted although whether inflammatory mediators play a central role in pathogenesis or a more minor secondary role has yet to be established. Despite this, numerous interventional studies, particularly targeting the complement system, are underway with the promise of novel therapeutic strategies for these important blinding conditions.